Rainstorm‑driven highly chlorine‑reactive DOM increases disinfection byproduct risks in drinking water - Zhengdi Wu; Pin Wang; Yu Lei; Yayun Zhang; Zhimin Qiang; Wenhai Chu (Water Research, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

Polyvinyl chloride microplastics disrupt spatial purification gradients and amplify antibiotic resistance risks in sulfamethoxazole-stressed constructed wetlands - Yu Xiao; Yangqi Liu; Xi Zhang; Jinping Cheng; Pin Gao (Chemical Engineering Journal, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Microplastics generation from PVC pipes in drinking water distribution systems: Effects of aging and flow conditions - Yu-Ming Liao; Bishwatma Biswas; Jenyuk Lohwacharin; Yi-Pin Lin (Journal of Environmental Management, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Self-healing chitosan-catechol hydrogel with tailored self-assembled fibrillar or micellar structures for biomedical applications - Pin-Yu Chen; Yuxuan Zhang; Shan-hui Hsu (Carbohydrate Polymers, 2026)

A digital-enabled circular recovery system for post-consumer inhalers: Linking material recovery, behaviour, and carbon reduction - Huong Thanh Hoang; Luong Cao Tung Son; Yu-Fen Huang; Ren-Hao Pan; Phuong Truc Nguyen Le; I-Chun Chuang; Huang-Chi Chen; Hung-Pin Tu; Chih-Hsing Hung; Da-Wei Wu (Journal of Cleaner Production, 2026)

Mapping climate-conditioned PM2.5 response under climate change in Taiwan using a high-resolution Geo-AI model - Pei-Yi Wong; Wei-Lun Hsu; Chieh-Ying Chen; Chien-Fei Chen; Chia-Wei Hsu; Shih-Chun Candice Lung; Ta-Chih Hsiao; Chia-Pin Yu; Wan-Yu Liu; Pau-Chung Chen; Wei Jie Seow; Chien-Hao Sung; et al. (Journal of Environmental Management, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Optimizing bubble tea packaging sustainability in Taipei: A life cycle assessment and multi-objective optimization approach for circular economy integration - Yan-Ruei Huang; Yu-Kai Liao; Ching-Pin Tung; Wei-Chun Chuang (Resources, Conservation and Recycling, 2026)

Inhibiting pyruvate carboxylase as a potential therapeutic strategy for alleviating rheumatoid arthritis - Szu-Wei Huang; Hui-Chun Yu; Hsien-Bin Huang; Pin-Chen Chen; Ming-Chi Lu (Inflammopharmacology, 2026)

Microbiological spectrum, clinical outcomes, and risk factors for bloodstream infections during immune checkpoint inhibitor therapy: a nested case-control study - Deng Pan; Huan Wang; Yu Fang; Jun Lu; Wendi Zhang; Pin Peng; Minghao Fang (Infectious Diseases, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Design Rules for Robust Coronary Artery Segmentation: A Systematic Analysis of Dataset Size, Windowing, Architectures, and Vessel Geometry - Ming-Hui Hung; Yu-Wei Chiang; Hao-Yun Liu; Han-Hsuan Chu; Yu-Sen Huang; Pin-Yi Chiang; Hsin-Ming Chen; Tzung-Dau Wang; Shyh-Jye Chen; Wen-Jeng Lee (Annals of Biomedical Engineering, 2026)

Projected impacts of climate change on the spatial distribution and habitat preference of tropical tuna in the Pacific Ocean - Yan-Lun Wu; Ting-Yu Liang; Wei-Pin Hsu; Teruhisa Shimada; Anindya Wirasatriya; Parichat Wetchayont; Chunhua Qiu; Kuo-Wei Lan (Marine Environmental Research, 2026)

Lipid accumulation by triphenylphosphine oxide with simultaneous neural dysregulation and microbiota changes - Youjia Liu; Yangyuan Zhou; Pin Gao; Zhenyang Yu; Daqiang Yin (Journal of Environmental Sciences, 2026)

Diversified rotation reduced N2O emissions by shaping N-cycling microbial communities and increasing their network complexity - Taobing Yu; Lang Cheng; Pin Wang; Lei Yang; Tengxiang Lian; Huadong Zang; Zhaohai Zeng; Yadong Yang (Journal of Environmental Sciences, 2026)

Machine learning and spatial regression approaches to estimating willingness to pay for ecosystem services in Jakarta and Taoyuan - Shafira Wuryandani; Yu-Pin Lin; Pei-Chen Lin; Dirk S. Schmeller; Gerard H. Ros (Ecosystem Services, 2026)

Numerical investigation of thermo-mechanical response and heat transfer in clay during thermal cone penetration testing - Jing Hu; Pin-Qiang Mo; Guo-Jun Cai; Zhao Lu; Abolfazl Eslami; Hai-Sui Yu (Computers and Geotechnics, 2026)

Social behavior of masked palm civet in an urban habitat - Po-Jun Chuang; Pin Xuan Lim; Shan-Min Chen; Pin-Huan Yu; Wei-Ting Liu; Hui-Yun Tseng (Mammal Research, 2026)

Analysis of the failure mechanisms and treatment effectiveness of the Houlang village landslide - Ke Wu Liao; Qing Yu Zhang; Qing Lü; Pin Hong Gao (Bulletin of Engineering Geology and the Environment, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

Ophiocordyceps Polyrhachicola (Hypocreales, Ophiocordycipitaceae), a New Species of Ant Associated Fungal Parasite in China - Jia‐Ping Wang; Chada Norphanphoun; Yu Yang; Yuan‐Pin Xiao; Kevin D. Hyde; Yong Wang (New Zealand Journal of Botany, 2026)
Ophiocordyceps , the largest genus within the family Ophiocordycipitaceae, is known for its parasitism on many insect hosts. Recent advances in global biodiversity research have enhanced the classification and ecological understanding of this genus, underscoring its pivotal role in global ecosystems. As the type genus of Ophiocordycipitaceae, Ophiocordyceps has undergone extensive taxonomic revision based on comprehensive studies. In this study, Ophiocordyceps polyrhachicola , a novel species from China that parasitizes the ants of the genus Polyrhachis inhabiting leaf litter of temperate deciduous forests is introduced. Species placement is supported corroborated by morphological observations and phylogenetic analyses of a multi‐locus dataset comprising ITS, LSU, SSU, rpb1 , rpb2 , and tef1‐α sequences. Detailed comparisons with closely related taxa reveal distinctive morphological traits and molecular characteristics, establishing O. polyrhachicola as a unique and well‐delimited species within the genus.

Consolidation characteristics of diatomaceous soil in coastal reclamations revealed by CPTu tests - Pin-Qiang Mo; Yu-cheng Li; Guojun Cai; Qiuzhu Ma; Hai-Sui Yu (Engineering Geology, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Deciphering dose-dependent effects of polypropylene and polyethylene microplastics on digestion performance dynamics and antibiotic resistance development in sludge anaerobic digesters - Yu Xiao; Yangqi Liu; Juan Zhou; Xiaoying Jiang; Pin Gao (Chemical Engineering Journal, 2026)

Exosome Purification Strategy Influences the Regenerative Efficacy of Dental Pulp Stem Cell-Derived Exosomes in Bone Regeneration - Borae Lee; Chia-Yi Hung; Yu-Ting Chien; Chi-Che Hsieh; Wei-Hao Cheng; Ya-Hui Chan; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

Release of microplastics from polyvinyl chloride pipes: Using accelerated aging by ozonation, chlorination and heating to assess the release potential - Yu-Teng Ji; Yi-Chin Cho; Jenyuk Lohwacharin; Yi-Pin Lin (Journal of Environmental Chemical Engineering, 2025)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Comparative analysis of deep learning models for cell counting in microalgae samples - Vimal Angela Thiviyanathan; Pin Jern Ker; Hassan Mohamed; Hasan Firdaus Mohd Zaki; Hui Jing Lee; Shirley G.H. Tang; Kai Ling Yu; Nazlina Haiza Mohd Yasin (Algal Research, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Structural and mechanistic insights into halogenated disinfection byproducts of tannic acid with toxicity analysis during chloramination - Shu-Xi Guo; Hui-Xian Hu; Pin Wang; Yu-En Guo; Yao Lu; Ye Du (Water Research, 2025)

Seismic evidence for magmatism-driven mud volcanism in the northern continental margin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Marine and Petroleum Geology, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

A novel sludge dewatering conditioner of chitin derivatives from waste black soldier fly puparia: Efficacy, key factors, and mechanisms - Junfeng Zhang; Yalin Yu; Wenhao Li; Pin Zhou; Nanwen Zhu; Shouqiang Huang; Amin Mojiri; Dongdong Ge (Process Safety and Environmental Protection, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Salinity-dependent responses differentiate branchial ion regulation during acute hypothermal stress in euryhaline Indian Medaka - Naveen Ranasinghe; Salman Akram; Shi-Shien Lee; Pin-Jhu Liao; Tsung-Jui Yang; Yu-Chieh Kung; Tsung-Han Lee; Chia-Jui Liu (Fish Physiology and Biochemistry, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Risk Perception and Adaptations to Flood Disaster in Coastal Tainan, Taiwan - Hsiao‐Wen Wang; Pin‐Han Kuo; Jie‐Wun Yu (Irrigation and Drainage, 2025)
The southwest coast of Taiwan is vulnerable to flooding. This study investigated flood risk perception and adaptive behaviour among residents of five coastal villages in coastal Tainan City, Taiwan, through a questionnaire survey yielding 97 valid responses. Descriptive and inferential statistics were employed to analyse demographic characteristics, disaster experience, risk perception and adaptive behaviour, and to examine differences across multiple variables. Results indicated the potential effectiveness of the flood‐resilient community programme in promoting adaptive behaviour, and highlighted the need for further in‐depth investigation to disentangle the factors influencing risk perception and adaptive behaviours. A significant positive relationship between understanding levels and the perceived helpfulness of preparedness information highlights the importance of effective information dissemination to enhance community resilience. Communication preferences have shifted toward mobile technologies for receiving timely warnings and preparedness information. Despite these findings, results indicated a persistent preference for engineering solutions and reliance on government infrastructure rather than personal preparedness. The study recommends a necessity for shared responsibility between the government and individuals, and emphasizes improving public risk perception related to flood preparedness and utilizing preferred communication channels to disseminate key information.

Towards sustainable construction: A cost-effective framework for bird monitoring from on-site collected videos leveraging deep active learning and synthetic training data - Hao Xu; Jun Kang Chow; Pin Siang Tan; Xin Mao; Kuan-fu Liu; Yu-Hsing Wang (Journal of Cleaner Production, 2025)

Hydraulic heterogeneity estimation with transient hydraulic tomography and convolutional encoder-decoder neural network - Yu-Kai Chen; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Antinociceptive Action of New Water-Soluble Molecule, a Representative of Hexaazaisowurtzitane Class - S. G. Krylova; E. A. Kiseleva; D. A. Kulagina; T. N. Povet’eva; P. V. Kul’pin; V. V. Eremina; N. A. Alekseeva; M. Yu. Minakova; E. P. Zueva; S. V. Sysolyatin; V. V. Zhdanov (Bulletin of Experimental Biology and Medicine, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Multi-hazard fragility analysis of cross-sea cable-stayed bridges cable bent tower under seismic-wind combined action - Yan Liang; Yu-zhen Kong; Li Yan; Zheng-hao Zhao; Pin-wu Guan (Soil Dynamics and Earthquake Engineering, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

In vivo molecular imaging of drug resistance in neuroblastoma using APE1 cyclically cleaved and miR-514a self-recycled programmable allosteric DNA nanomachine - Wancun Zhang; Zhenzhen Tian; Pin Zhang; Lifeng Li; Zhidan Yu; Meng Sun; Kangbo Liu; Ligong Hou; Jie Zhang; Mengxin Zhang; Xianwei Zhang (Chemical Engineering Journal, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Challenges and opportunities in using biowaste for sustainable hydroponic netted melon (Cucumis melo L.) cultivation - Yen-Tzu Fan; Zih-Ee Lin; Pei-Te Chiueh; Yu-Pin Lin; Lien-Chieh Cheng; Yu-Shen Cheng; Shu-I Lin; Chihhao Fan (Agricultural Systems, 2025)

Quantitative analysis of anthocyanins and flavonoids in purple and green leaves of Eleutherococcus senticosus by UPLC-MS/MS techniques - Mei Hua; Meng Meng; Yu-pin Fu; Yun-qin Li (Natural Product Research, 2025)

Loss of circular EYA3 attenuates formaldehyde-induced cardiomyocyte pyroptosis and congenital heart defects by regulating Smad5 stability - Ying Zhang; Yanyan Yang; Xiangqin He; Pin Sun; Xiaoxia Song; Yu Tian; Jianmin Ma; Ruicong Sun; Tao Yu; Zhirong Jiang (Science of The Total Environment, 2025)

Estimating basin-scale heterogeneous hydraulic diffusivity fields based on signal decomposition and river stage tomography - Bo-Tsen Wang; Yu-Li Wang; Chia-Hao Chang; Chin-Tsai Hsiao; Jordi Mahardika Puntu; Ping-Yu Chang; Jui-Pin Tsai (Journal of Hydrology, 2025)

Enhanced SERS performance through defect-guided growth of 2D/3D AuAg nanoplates for chemical sensing and cellular imaging applications - Kuan-Wen Liu; Pei-Yu Sie; Hsi-Ying Chen; Fong-I Ho; Po-Sheng Huang; Pin Chieh Wu; Mei-Yi Liao (Analytica Chimica Acta, 2025)

Exploring the oral bacteria-oral lichen planus connection: mechanisms, clinical implications and future directions - Wei-long Zhang; Lian-pin Yu; Wei Zhou; Xue Wang; Juan Du (Archives of Microbiology, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

A Comprehensive Investigation of Physics-Informed Learning in Forward and Inverse Analysis of Elastic and Elastoplastic Footing - Xiao-Xuan Chen; Pin Zhang; Zhen-Yu Yin (Computers and Geotechnics, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Enrichment and characterization of foodborne fungal spores by ferric ion-based surface-assisted laser desorption/ionization mass spectrometry - Tzu-Ling Yang; Chih-Wei Chen; Noor Hidayat Abu Bakar; Pin-Chen Pan; Po-Hung Cheng; Yu-Chie Chen (Food Chemistry, 2025)

A novel MOF-on-MOF-derived carbon-encapsulated CeO2/Co/Co3O4 humidity-resistant heterojunction with abundant oxygen vacancies for efficient ozone removal - Abiyu Kerebo Berekute; An-Yu Wang; Kun-Yi Lin; Sepridawati Siregar; Kuo-Pin Yu (Environmental Research, 2025)

Effects of forest bathing and the influence of exposure levels on cognitive health in the elderly: Evidence from a suburban forest recreation area - Jittakon Ramanpong; Chen Tsao; Jie Yin; Chih-Da Wu; Yu-Chih Huang; Chia-Pin Yu (Urban Forestry & Urban Greening, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Involvement of Receptor Apparatus in the Realization of Antinociceptive Activity of Songorine - Yu. V. Nesterova; A. V. Mukhomedzyanov; T. N. Povetyeva; N. I. Suslov; P. V. Kul’pin; O. G. Afanas’eva; A. V. Vychuzhanina; O. Yu. Rybalkina; G. N. Zyuz’kov; V. V. Zhdanov; M. Yu. Minakova (Bulletin of Experimental Biology and Medicine, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Metal ions-mediated concerted electron-proton transfer enables catalytic oxidation of phenolic contaminants by permanganate - Tiansheng Chen; Pin Xie; Yanghai Yu; Xiaoguang Duan; Yuankui Sun; Xiaohong Guan (Water Research, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

Synergising hydrothermal pre-treatment and biological processes for enhancing biohydrogen production from palm oil mill effluent - Bidattul Syirat Zainal; Kai Ling Yu; Hwai Chyuan Ong; Hassan Mohamed; Pin Jern Ker; G. Abdulkreem-Alsultan; Yun Hin Taufiq-Yap; TM Indra Mahlia (Process Safety and Environmental Protection, 2024)

Diphosphonic ionic liquids as anion-exchangers for palladium(II) and platinum(IV): Synthesis, complexation and selective extraction from hydrochloric solutions - Anna Yu. Fominykh; Pin-Wen Huang; Leonid Yu. Starostin; Paulina Kalle; Natalia E. Borisova; Wei-Qun Shi; Petr I. Matveev (Journal of Environmental Chemical Engineering, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Association between long-term PM2.5 exposure and mortality on Sumatra Island: Indonesian Family Life Survey (IFLS) 2000–2014 - Sepridawati Siregar; Nora Idiawati; Abiyu Kerebo Berekute; Muchsin Maulana; Wen-Chi Pan; Kuo-Pin Yu (Environmental Monitoring and Assessment, 2024)
The concentration of PM 2.5 (particulate matter with a diameter < 2.5 µm) on Sumatra Island has increased, mainly because of forest and peatland fires, transportation, and industry. Biomass burning releases partially burned carbon into the atmosphere, resulting in a smoky haze containing PM 2.5 . Air quality has deteriorated quickly, and PM 2.5 has become a major health hazard in Indonesia. Studies on long-term exposure to PM 2.5 have indicated its associations with both morbidity and mortality. Here, we measured long-term (2000–2014) exposure to PM 2.5 on the basis of satellite-derived aerosol optical depth measurements (1 × 1 km 2 ) used to predict ground-level PM 2.5 concentrations. Additionally, population data on Sumatra Island residents from the fourth wave of the Indonesian Family Life Survey (IFLS) were obtained. We investigated the association between long-term PM 2.5 exposure and mortality with a retrospective cohort study design. A total of 2409 subjects aged ≥ 40 years participated in the IFLS-3 beginning in November 2000, and we examined mortality outcomes until the IFLS-5 in September 2014. We used Cox regression models to calculate hazard ratios (HRs) of mortality associated with PM 2.5 exposure. According to the adjusted model, the mortality HRs per 10 µg/m 3 increase in PM 2.5 concentration were 1.10 (95% CI 1.03, 1.17) for all natural causes, 1.17 (95% CI 1.05, 1.25) for cardiovascular causes, and 1.19 (95% CI 1.04, 1.36) for respiratory causes. Long-term exposure to PM 2.5 was associated with all-natural, cardiovascular, and respiratory mortality on Sumatra Island, where PM 2.5 levels exceed the WHO and US-EPA air quality standards.

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Towards automatic urban tree inventory: Enhancing tree instance segmentation via moving object removal and a chord length-based DBH estimation approach - Wai Yi Chau; Jun Kang Chow; Tun Jian Tan; Jimmy WU; Mei Ling Leung; Pin Siang Tan; Siu Wai Chiu; Billy Chi Hang Hau; Hok Chuen Cheng; Yu-Hsing Wang (Computers and Electronics in Agriculture, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Possible toxification mechanisms of acute and chronic pentachlorophenol to Montipora digitata: Limitation of energy supply and immunotoxicity - Lan Luo; Pengfei Xue; Xuan Chen; Pin Gan; Xiaoli Li; Kefu Yu; Yuanyuan Zhang (Science of The Total Environment, 2024)

Effects of polypropylene microplastics on digestion performance, microbial community, and antibiotic resistance during microbial anaerobic digestion - Yu Xiao; Yan Qin; Xiaoying Jiang; Pin Gao (Bioresource Technology, 2024)

Treatment of arsenic-contaminated groundwater with a novel iron oxide/carbon composite as the adsorbent - Hung-Hsiang Chen; Yu-Chen Chang; Wei-Kuo Wei; Yung-Pin Tsai; Chih-Chi Yang; Ku-Fan Chen (Water, Air, & Soil Pollution, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Effects of Attachment Design and Aligner Material on Mandibular Canine Distal Bodily Movement in Aligner Treatment - Pin-Yu Chen; Heng-Li Huang; Jian-Hong Yu; Jui-Ting Hsu (Journal of Medical and Biological Engineering, 2024)
Purpose Dental crowding is a result of a mismatch between tooth size and arch dimensions, which leads to malocclusion; treatment often involves premolar extraction before orthodontic alignment. Clear aligners are limited in their ability to achieve canine distal bodily movement, a common orthodontic maneuver. This study investigated the impacts of attachment design and aligner material on the efficacy of canine distal bodily movement. Methods A finite element analysis was conducted to examine the impact of various attachment designs and two aligner materials, thermoplastic polyurethanes/polycarbonate (TPU/PC) and polyethylene terephthalate glycol-modified (PETG), on mandibular canine distal bodily movement. The investigation focused on the biomechanical responses in the periodontal ligament (PDL) and surrounding alveolar bone. Results Attachment configuration exerted a strong influence on mandibular canine movement. Vertically oriented attachment pairs positioned mesially (mesial occlusal–mesial cervical) resulted in the most effective canine distal bodily movement, followed by a rectangular attachment. TPU/PC aligners induced slightly higher principal stresses in the PDL and von Mises stress and strain in the surrounding alveolar bone compared with PETG aligners; however, the difference was negligible, amounting to less than 6%. Conclusion Attachment design, specifically vertically oriented pairs positioned mesially (mesial occlusal–mesial cervical), was determined to be the crucial factor influencing the efficacy of canine distal bodily movement. The choice of aligner material (TPU/PC or PETG) has minimal impact on this orthodontic procedure.

Comparison of the inactivation of Uronema marinum in mariculture by UV/chlorine, UV/monochloramine, and UV/chlorine dioxide: Efficiency, mechanism and feasibility - Pin Gan; Xuan Chen; Yuanyuan Zhang; Xudong Li; Fangyu Liang; Tianhao Wu; Pengfei Xue; Kefu Yu (Journal of Water Process Engineering, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Analytical solution for transient radial interaction between energy piles and soils: Thermo-elastic cavity expansion analysis - He Yang; Pei-Zhi Zhuang; Pin-Qiang Mo; Hai-Sui Yu; Xiaohui Chen (Geomechanics for Energy and the Environment, 2024)

Detection of a mud volcano in the Weitan Banks area of the northern South China Sea - Wei Luo; Pin Yan; Yanlin Wang; Junhui Yu; Qionghua Wan; Zhenbo Zhang; Tao Xue (Journal of Oceanology and Limnology, 2024)

Assessment of air pollution emitted during cooking using biomass and cleaner fuels in the Shiselweni region of Eswatini (Swaziland) - Melinda Neumann; Wonder Nathi Dlamini; Rasham Sallah-Ud-Din; Abiyu Kerebo Berekute; Sepridawati Siregar; Mastewal Endeshaw Getnet; Muchsin Maulana; Wen-Chi Pan; Shih-Chun Candice Lung; Kuo-Pin Yu (Clean Technologies and Environmental Policy, 2024)
In Eswatini, 62.3% of households still rely on solid fuel for cooking, especially wood (61.8%). Smoke emissions during biomass burning remain the primary source of indoor air pollution, comprising pollutants detrimental to health. This study provides a quantitative exposure assessment of fuels used in the Shiselweni region with the objectives of monitoring the carbon monoxide (CO) and carbon dioxide (CO 2 ) concentrations during cooking events and evaluating cancer and noncancer risks due to exposure to particulate-bound polycyclic aromatic hydrocarbons (PAHs) during cooking events among cooking personnel in households that cook indoors by burning biomass. Real-time CO, CO 2, and particulate matter (PM) monitoring was performed in seventeen kitchens during cooking events across the Shiselweni region using different cooking methods: biomass in open fires and stoves, liquefied petroleum gas (LPG), and electric stoves. PM 2.5 , PM 10, and CO exceeded indoor exposure guidelines for biomass fuel-related homesteads. Particulate PAH intake concentrations were evaluated, and biomass fuel users exhibited high cancer risks and low embryo survival chances due to particulate PAH exposure. The average total cost of reducing the incremental lifetime cancer risk (ILCR) and hazard quotient (HQ) to acceptable levels was lower when shifting from biomass to LPG stoves than when shifting to electric stoves. Graphical abstract

Comparative Study of the Anxiolytic Activity of Songorine in Elevated Plus Maze Test and by Recording Ultrasonic Vocalizations - Yu. V. Nesterova; O. V. Vsyakikh; P. V. Kul’pin; T. N. Povetyeva; G. N. Zyuz’kov; N. I. Suslov; V. V. Zhdanov; E. A. Losev (Bulletin of Experimental Biology and Medicine, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

Novel multi-spatial receptive field (MSRF) XGBoost method for predicting geological cross-section based on sparse borehole data - Yashi Qiu; Ning Zhang; Zhenyu Yin; Yu Wang; Changjie Xu; Pin Zhang (Engineering Geology, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

1300-m-High gas plume from pockmarks in the north Nansha waters, South China sea - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Jinfeng Ma; Zhuangcai Tian; Changliang Chen (Marine and Petroleum Geology, 2024)

Enhanced removal of viral aerosols using nanosilver/TiO2-chitosan filters combined with a negative air ionizer - Wonder Nathi Dlamini; Ting-Ching Yao; Hsin-Jui Lee; Abiyu Kerebo Berekute; Rasham Sallah-Ud-Din; Sepridawati Siregar; Kuo-Pin Yu (Journal of Environmental Chemical Engineering, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

Late Holocene paleoclimate reconstruction of northern Taiwan using a multiproxy approach in the Dream Lake sediment core - Abdur Rahman; Wei-Cheng Chang; Kaoru Kashima; Yu Fukumoto; Jyh-Jaan Steven Huang; Ludvig Löwemark; Liang-Chi Wang; Yuan-Pin Chang (Quaternary International, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

The health risk reduction of PM2.5 via a green curtain system in Taiwan - Yi Hsing Chang; Ting-Hsuan Chen; Hsin-Ying Chung; Hsi-Yu Hsiao; Pin-Chieh Tseng; Yu-Chun Wang; Shih-Chun Candice Lung; Huey-Jen Su; Yaw-Shyan Tsay (Building and Environment, 2024)

Itaconate inhibits corticosterone-induced necroptosis and neuroinflammation via up-regulating menin in HT22 cells - Jin-Yu Liang; Shan Gao; Jia-Mei Jiang; Pin Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Journal of Physiology and Biochemistry, 2024)

Corrigendum to “Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment” [Urban For. Urban Green. 87 (2023) 1–9/128066] - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Photochemical oxidation of VOCs and their source impact assessment on ozone under de-weather conditions in Western Taiwan - Manisha Mishra; Pin-Hsin Chen; Guan-Yu Lin; Thi-Thuy-Nghiem Nguyen; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Shih-Heng Shih; Ciao-Wei Jhang; Chuen-Jinn Tsai (Environmental Pollution, 2024)

The potential of a multi-fidelity residual neural network based optimizer to calibrate DEM parameters of rock-like bonded granular materials - Zhihao Zhou; Zhen-Yu YIN; Geng-Fu He; Pin Zhang; Mingjing Jiang (Computers and Geotechnics, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Acute hepatic and kidney injury after ingestion of Lepiota brunneoincarnata: Report of 2 cases - JiaJu Zhong; Pin Xu; HaiJiao Li; ChengYe Sun; Yun Tong; QunMei Yao; ChengMin Yu (Toxicon, 2024)

Do greenness and landscape indices for greenspace correlate with suicide ratio? - Hsiao-Yun Lee; Hao-Ting Chang; Samuel Herianto; Chi-Shin Wu; Wan-Yu Liu; Chia-Pin Yu; Wen-Chi Pan; Chih-Da Wu (Landscape and Urban Planning, 2024)

Assessment of sediment transport in Luxiapuqu watershed using RUSLE-TLSD and InSAR techniques: Yarlung Tsangpo River, China - Hao-Shuang Chen; Ling Lan; Yi-Pin Nie; Yu-Ge Wang; Xie-Kang Wang (Environmental Science and Pollution Research, 2024)

Exposure to pentachlorophenol destructs the symbiotic relationship between zooxanthellae and host and induces pathema in coral Porites lutea - Yuanyuan Zhang; Lan Luo; Pin Gan; Xuan Chen; Xiaoli Li; Yan Pang; Xiaopeng Yu; Kefu Yu (Science of The Total Environment, 2024)

V-ATPase E mediates Cry2Ab binding and toxicity in Helicoverpa armigera - Yuge Zhao; Pin Li; Xue Yao; Yuepu Li; Yu Tian; Guiying Xie; Zhongyuan Deng; Shuxia Xu; Jizhen Wei; Xianchun Li; Shiheng An (Pesticide Biochemistry and Physiology, 2024)

Physiological and psychological responses to transitions between urban built and natural environments using the cave automated virtual environment - Di Chen; Jie Yin; Chia-Pin Yu; Shengjing Sun; Charlotte Gabel; John D. Spengler (Landscape and Urban Planning, 2024)

Subsurface structures and nature of seafloor mounds in the northern South China Sea margin: Implications for Mesozoic hydrocarbon exploration - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Geomorphology, 2024)

Efficient degradation of fluoroquinolone antibiotics in the landfill leachate by sludge biochar activated peracetic acid: Radical vs non-radical process - Zilin Zhou; Yan Yang; Gang Xue; Yang Yu; Jiabin Chen; Pin Gao; Yajie Qian (Chemical Engineering Journal, 2024)

Genetic diversity and relatedness of feline parvovirus in Vietnam and its potential implications for canine-feline transmission - Hoang Minh; Nguyen Vu Son; Hoang Minh Duc; Chao-Nan Lin; Yu-Chung Tyan; Kuo-Pin Chuang (Archives of Virology, 2024)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Inactivation of Heterosigma akashiwo under UV/peroxydisulfate advanced disinfection system in marine waters - Xuan Chen; Kunling Huang; Pin Gan; Lan Luo; Kefu Yu; Yuanyuan Zhang; Yunfeng Pang; Pengfei Xue (Chemosphere, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

A novel pulse-decay-balance method for smooth rock joint aperture measurement - Xuan-Xinh Nguyen; Pin-Lun Tai; Jia-Jyun Dong; Chi-Wen Yu (International Journal of Rock Mechanics and Mining Sciences, 2023)

Novel visible-light-active P-g-CN-based α-Bi2O3/WO3 ternary photocatalysts with a dual Z-scheme heterostructure for the efficient decomposition of refractory ultraviolet filters and environmental hormones: Benzophenones - Abiyu Kerebo Berekute; Kuo-Pin Yu; Yi-Hsueh Brad Chuang; Kun-Yi Andrew Lin (Environmental Research, 2023)

High-efficiency carbon-coated steel wool filter for controlling cooking-induced oil smoke - Ho-Sheng Wei; Abiyu Kerebo Berekute; Sepridawati Siregar; Kuo-Pin Yu (Environmental Pollution, 2023)

Impact of Taiwan’s 2021 COVID-19 lockdown on the symptom severity and quality of life of patients with narcolepsy - Wei-Chih Chin; Yu-Shu Huang; I. Tang; Pin-Yi Lee; Chih-Huan Wang; Kuo-Yu Chao (Sleep and Biological Rhythms, 2023)

AI-IoT integrated framework for tree tilt monitoring: A case study on tree failure in Hong Kong - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau (Agricultural and Forest Meteorology, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

Thermodynamic sensitivity of ammonia oxidizers-driven N2O fluxes under oxic-suboxic realms - Hussnain Mukhtar; Andrianto Ansari; Thanh Ngoc-Dan Cao; Rainer Ferdinand Wunderlich; Yu-Pin Lin (Chemosphere, 2023)

Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2023)

Source-apportionment and spatial distribution analysis of VOCs and their role in ozone formation using machine learning in central-west Taiwan - Manisha Mishra; Pin-Hsin Chen; Wilfredo Bisquera; Guan-Yu Lin; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Ciao-Wei Jhang; Ci-Jhen Wu; Chuen-Jinn Tsai (Environmental Research, 2023)

Discrete element modelling of thermal penetration test with heating and cooling - Pin-Qiang Mo; Jing Hu; Yu-Chen Hu; Kuan-Jun Wang; Abolfazl Eslami; Liu Gao (Computers and Geotechnics, 2023)

Arginase from Priestia megaterium and the Effects of CMCS Conjugation on Its Enzymological Properties - Yu Liang Jiao; Pin Quan Shen; Shu Fang Wang; Jing Chen; Xiang Hong Zhou; Gui Zhen Ma (Current Microbiology, 2023)

Elastic scattering dominates high-frequency seismic attenuation in Southern California - Yu-Pin Lin; Thomas H. Jordan (Earth and Planetary Science Letters, 2023)

Interpretable data-driven constitutive modelling of soils with sparse data - Pin Zhang; Zhen-Yu Yin; Brian Sheil (Computers and Geotechnics, 2023)

Nutritional and ameliorative effects of dietary curcumin and its nano-silica and nano-zeolite encapsulated forms on growth, biochemical and fatty acid profile of common carp (Cyprinus carpio) - Shadieh Moradi; Samyar Ashouri; Fereshteh Pirani; Seyed Ali Johari; Hoi Pin Kim; Il Je Yu; Edris Ghaderi (Fish Physiology and Biochemistry, 2023)

Soil microbiome feedback to climate change and options for mitigation - Hussnain Mukhtar; Rainer Ferdinand Wunderlich; Adnan Muzaffar; Andrianto Ansari; Oleg V. Shipin; Thanh Ngoc-Dan Cao; Yu-Pin Lin (Science of The Total Environment, 2023)

Association between ambient air pollutant interaction with kidney function in a large Taiwanese population study - Wei-Yu Su; Da-Wei Wu; Hung-Pin Tu; Szu-Chia Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

The Coorg Block, southern India: Insights from felsic and mafic magmatic suites on Mesoarchean plate tectonics and correlation with supercontinent Ur - Cheng-Xue Yang; M. Santosh; Jarred C. Lloyd; Stijn Glorie; Pin Gao; Bing Yu; Y. Anilkumar; K.S. Anoop; Sung-Won Kim (Gondwana Research, 2023)

Ecofriendly removal of Lead, Cadmium and Arsenic along with turbidity from contaminated water using natural reservoir clay (NRC) and S. pasteurii derived urease - Jyoti Prakash Maity; Yung-Ping Chen; Jirawadee Promsri; Yi-Hsun Huang; Raju Kumar Sharma; Yu-Hui Chen; Pin-Yun Lin; Marut Tangwattanachuleeporn; Kulwara Poolpol; Tsung-Hsien Chen; Chien-Yen Chen (Desalination, 2023)

Development of a rigorous and generalized model on the hydrothermal liquefaction (HTL) process for bio-oil production - Yuan-Pin Shia; Bor-Yih Yu (Process Safety and Environmental Protection, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Origin of a giant fuzzy reflection zone and its implication for natural gas exploration in the southwestern Qiongdongnan Basin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Yan Qiu; Guanghong Tu; Changliang Chen (Journal of Oceanology and Limnology, 2023)

Discovery of pockmarks in the Zengmu Basin, southern South China Sea and the implication - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Yongbin Jin; Changliang Chen; Jie Liu (Journal of Oceanology and Limnology, 2023)

Blue carbon science, management and policy across a tropical urban landscape - Daniel A. Friess; Yasmine M. Gatt; Tze Kwan Fung; Jahson B. Alemu; Natasha Bhatia; Rebecca Case; Siew Chin Chua; Danwei Huang; Valerie Kwan; Kiah Eng Lim; Yudhishthra Nathan; Yan Xiang Ow; et al. (Landscape and Urban Planning, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Editorial: Coastal environmental and ecological data analysis - Meilin Wu; Yu-Pin Lin; Ana Carolina Ruiz-Fernández; Biraja Kumar Sahu (Frontiers in Marine Science, 2023)

Geophysical evidence for a serpentine mud volcano in the relict slow-spreading center of the South China Sea - Yanlin Wang; Pin Yan; Junhui Yu; Guanghong Tu; Jun Wang; Yan Qiu; Changliang Chen (Tectonophysics, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Using recoverable sulfurized magnetic biochar for active capping to remediate multiple heavy metal contaminated sediment - Che-Jung Hsu; Yung-Hua Cheng; Adrienne Chung; Ying-Pin Huang; Yu Ting; Hsing-Cheng Hsi (Environmental Pollution, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Antinociceptive Effect of Ethowurtzine, a New Compound from the Class of Hexaazaizowurzitane - S. G. Krylova; E. A. Kiseleva; T. N. Povet’eva; Yu. V. Nesterova; O. Yu. Rybalkina; P. V. Kul’pin; O. G. Afanas’eva; D. A. Kulagina; V. V. Eremina; O. V. Baibakova; E. P. Zueva; N. I. Suslov; et al. (Bulletin of Experimental Biology and Medicine, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

Optimal Design of the Seepage Control for Xianglushan Diversion Tunnel Under High External Water Pressure - Zhen-jie Zhang; Chun-pin Zeng; Hu Li; Yang Gao; Liang Gong; Yu-xing Li; Hai-fang Liang; En-zhong Zhang (Geotechnical and Geological Engineering, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Paleolimnological evidence for lacustrine environmental evolution and paleo-typhoon records during the late Holocene in eastern Taiwan - Liang-Chi Wang; Yu-Min Chou; Huei-Fen Chen; Yuan-Pin Chang; Hong-Wei Chiang; Tien-Nan Yang; Liang-Jian Shiau; Yue-Gau Chen (Journal of Paleolimnology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Association between satellite-based estimates of long-term PM2.5 exposure and cardiovascular disease: evidence from the Indonesian Family Life Survey - Sepridawati Siregar; Nora Idiawati; Wen-Chi Pan; Kuo-Pin Yu (Environmental Science and Pollution Research, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Dietary supplementation with curcumin nanomicelles, curcumin, and turmeric affects growth performance and silver nanoparticle toxicity in Cyprinus carpio - Fereshteh Pirani; Shadieh Moradi; Samyar Ashouri; Seyed Ali Johari; Edris Ghaderi; Hoi Pin Kim; Il Je Yu (Environmental Science and Pollution Research, 2021)

Magnetic porous biochar as a renewable and highly effective adsorbent for the removal of tetracycline hydrochloride in water - Hucheng Yang; Hao Yu; Jiahao Wang; Tao Ning; Pin Chen; Jing Yu; Siyuan Di; Shukui Zhu (Environmental Science and Pollution Research, 2021)

Three-dimensional Spheroid Culture Enhances Multipotent Differentiation and Stemness Capacities of Human Dental Pulp‐derived Mesenchymal Stem Cells by Modulating MAPK and NF-kB Signaling Pathways - Ya-Hui Chan; Yu-Chieh Lee; Chia-Yi Hung; Pi-Ju Yang; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2021)

Genetic improvement for aquaculture species: A promising approach for aquaculture challenges and development - Zhen‐Yu Du; Pin Nie; Jiashou Liu (Reviews in Aquaculture, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Deep convolutional neural network–based pixel-wise landslide inventory mapping - Zhaoyu Su; Jun Kang Chow; Pin Siang Tan; Jimmy Wu; Ying Kit Ho; Yu-Hsing Wang (Landslides, 2021)

Some Aspects of Investigation of the Central Mechanism of Antinociceptive Effect of a New Analgetic from the Hexaazaisowurtzitane Group - S. G. Krylova; K. A. Lopatina; Yu. V. Nesterova; T. N. Povet’eva; P. V. Kul’pin; O. G. Afanas’eva; D. A. Kulagina; E. A. Safonova; E. P. Zueva; N. I. Suslov; S. V. Sysolyatin (Bulletin of Experimental Biology and Medicine, 2021)

Eliminating vascular interference from the Spot Sign contributes to predicting hematoma expansion in individuals with spontaneous cerebral hemorrhages - Pan Yi; Min Xu; Pin Chen; Yu Luo; Dongdong Wang; Hui Wang; Cunzu Wang (Acta Neurologica Belgica, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Flavobacterium ajazii sp. nov., Isolated from Seaweed of Gouqi Island, China - Ishrat Khan; Sanjit Chandra Debnath; Cen Yan; Can Chen; Yan Xu; Wen-Jie Wang; Yu-Chao Yu; Dao-Qiong Zheng; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2020)

Integrated control of potato late blight with a combination of the photosynthetic bacterium Rhodopseudomonas palustris strain GJ-22 and fungicides - Xin Zhang; Xiaonian Li; Yu Zhang; Yue Chen; Xinqiu Tan; Pin Su; Deyong Zhang; Yong Liu (BioControl, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Transnasal endoscopic treatment on a rare case of intracranial penetrating brain injury - Min Xu; Yu Luo; Pin Chen; Pan Yi; Cun-zu Wang (Acta Neurologica Belgica, 2020)

Mode of silver clearance following 28-day inhalation exposure to silver nanoparticles determined from lung burden assessment including post-exposure observation periods - Mi Seong Jo; Jin Kwon Kim; Younghun Kim; Hoi Pin Kim; Hee Sang Kim; Kangho Ahn; Ji Hyun Lee; Elaine M. Faustman; Mary Gulumian; Bruce Kelman; Il Je Yu (Archives of Toxicology, 2020)

Particulates and particulates-bound mercury (Hg(p)) sizes (PM18, PM10, PM2.5, PM1, PM<1) distributions study by using MOUDI sampler at a complex sampling site - Guor-Cheng Fang; Chao-Lang Kao; Pin-Wen Huang; Huang-Min Chen; Yu-Lun Wu; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

LncRNA TUG1 promoted osteogenic differentiation through promoting bFGF ubiquitination - Yang Yu; Ying Chen; Yi-jing Zheng; Qi-hao Weng; Si-pin Zhu; Dong-sheng Zhou (In Vitro Cellular & Developmental Biology - Animal, 2020)

LpxD gene knockout elicits protection to Litopenaeus vannamei, white shrimp, against Vibrio parahaemolyticus infection - Ching-Yi Tsai; Harvey M. Santos; Shao-Yang Hu; Cheng Yu Sang; Ciara Alyssa S. Yanuaria; Ernest Nicolo G. Lola; Lemmuel L. Tayo; Karmella Marie A. Nitura; Chun Hung Liu; Kuo Pin Chuang (Aquaculture International, 2019)

Evolution of Broken Coal Permeability Under the Condition of Stress, Temperature, Moisture Content, and Pore Pressure - Jiangkun Chao; Minggao Yu; Tingxiang Chu; Xuefeng Han; Fei Teng; Pin Li (Rock Mechanics and Rock Engineering, 2019)

Effects of vermicomposting on the main chemical properties and bioavailability of Cd/Zn in pure sludge - Jizhou Zhang; Maral Erdene Sugir; Yunying Li; Lei Yuan; Meng Zhou; Pin Lv; Zhimin Yu; Limin Wang; Dongxing Zhou (Environmental Science and Pollution Research, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Stochastic competitive analysis of hydropower and water supplies within an energy–water nexus - Ming-Che Hu; Tailin Huang; Hwa-Lung Yu; Ching-Pin Tung (Stochastic Environmental Research and Risk Assessment, 2018)

Anti-Oxidative Effects of Melatonin Receptor Agonist and Omega-3 Polyunsaturated Fatty Acids in Neuronal SH-SY5Y Cells: Deciphering Synergic Effects on Anti-Depressant Mechanisms - Senthil Kumaran Satyanarayanan; Yin-Hwa Shih; Yu-Chuan Chien; Shih-Yi Huang; Piotr Gałecki; Siegfried Kasper; Jane Pei-Chen Chang; Kuan-Pin Su (Molecular Neurobiology, 2018)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Effect of Lithium Preparations on Cerebral Electrophysiological Activity in Rats - V. I. Konenkov; L. N. Rachkovskaya; A. Yu. Letyagin; N. I. Suslov; A. V. Shurlygina; M. V. Robinson; M. A. Korolev; A. A. Kotlyarova; T. V. Popova; E. E. Rachkovskii; T. N. Povet’eva; N. V. Shilova; et al. (Bulletin of Experimental Biology and Medicine, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Correction of Cholinergic Abnormalities in Mnestic Processes with Diterpene Alkaloid Songorine - Yu. V. Nesterova; T. N. Povet’eva; N. I. Suslov; G. N. Zyuz’kov; V. V. Zhdanov; Yu. S. Fedorova; P. V. Kul’pin; K. V. Shaposhnikov (Bulletin of Experimental Biology and Medicine, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Effects of liquid layers and distribution patterns on three-phase saturation and relative permeability relationships: a micromodel study - Jui-Pin Tsai; Liang-Cheng Chang; Shao-Yiu Hsu; Hsin-Yu Shan (Environmental Science and Pollution Research, 2017)

Photocatalytic decomposition of indoor ozone motivated by the white-light-emitting diode - Jia-You Gong; Yen-Chi Chen; Kuo-Pin Yu (Clean Technologies and Environmental Policy, 2017)

Psychopharmacological Effects of JNK Inhibitor in Posthypoxic Encephalopathy and Mechanisms of Their Development - G. N. Zyuz’kov; N. I. Suslov; T. N. Povet’eva; Yu. V. Nesterova; O. G. Afanas’eva; E. V. Udut; L. A. Miroshnichenko; E. V. Simanina; T. Yu. Polyakova; L. A. Stavrova; A. V. Chaikovskii; P. V. Kul’pin; et al. (Bulletin of Experimental Biology and Medicine, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Erratum to: The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

A New Schiff Base Chemodosimeter: Selective Colorimetric and Fluorescent Detection of Fe (III) Ion - Yu-Kuan Chiang; Yeshwant Ramchandra Bhorge; Rupesh D. Divate; Yun-Chin Chung; Yao-Pin Yen (Journal of Fluorescence, 2016)

Resistance to Pythium irregulare root and hypocotyl disease in diverse common bean (Phaseolus vulgaris) varieties from 37 countries and relationships to waterlogging tolerance and other plant and seed traits - Yu Pin Li; Ming Pei You; Sally Norton; Martin J. Barbetti (European Journal of Plant Pathology, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Imaging Rainfall Infiltration Processes with the Time-Lapse Electrical Resistivity Imaging Method - Gang Zhang; Gui-Bin Zhang; Chien-chih Chen; Ping-Yu Chang; Tzu-Pin Wang; Horng-Yuan Yen; Jia-Jyun Dong; Chuen-Fa Ni; Su-Chin Chen; Chao-Wei Chen; Zheng-yuan Jia (Pure and Applied Geophysics, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea - Zheng Hong-Bo; Yan Pin; Yan-Lin Wang; Yu-Qing Xing (Marine Georesources & Geotechnology, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Ontogenetic development of adipose tissue in grass carp (Ctenopharyngodon idellus) - Pin Liu; Hong Ji; Chao Li; Jingjing Tian; Yifei Wang; Ping Yu (Fish Physiology and Biochemistry, 2015)

The assessment of high recharge areas using DO indicators and recharge potential analysis: a case study of Taiwan’s Pingtung plain - Jui-Pin Tsai; Yu-Wen Chen; Liang-Cheng Chang; Wen-Fu Chen; Chung-Jung Chiang; You-Cheng Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

The versatile roles of CARDs in regulating apoptosis, inflammation, and NF-κB signaling - Wen-Pin Kao; Chao-Yu Yang; Tsung-Wei Su; Yin-Ting Wang; Yu-Chih Lo; Su-Chang Lin (Apoptosis, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

Probabilistic framework for assessing the arsenic exposure risk from cooked fish consumption - Min-Pei Ling; Chiu-Hua Wu; Szu-Chieh Chen; Wei-Yu Chen; Chia-Pin Chio; Yi-Hsien Cheng; Chung-Min Liao (Environmental Geochemistry and Health, 2014)

The development of stream temperature model in a mountainous river of Taiwan - Ching-Pin Tung; Tsung-Yu Lee; Jr-Chuang Huang; Po-Wen Perng; Shih-Ji Kao; Lin-Yen Liao (Environmental Monitoring and Assessment, 2014)

The complete mitochondrial genome of the brown leg mite, Aleuroglyphus ovatus (Acari: Sarcoptiformes): evaluation of largest non-coding region and unique tRNAs - En-Tao Sun; Chao-Pin Li; Liu-Wang Nie; Yu-Xin Jiang (Experimental and Applied Acarology, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Associations of T helper 1, 2, 17 and regulatory T lymphocytes with mortality in severe sepsis - Huang-Pin Wu; Kong Chung; Chun-Yao Lin; Bor-Yiing Jiang; Duen-Yau Chuang; Yu-Chih Liu (Inflammation Research, 2013)

Dissection of the role of Pinin in the development of zebrafish posterior pharyngeal cartilages - Shu-Yuan Hsu; Yi-Chuan Cheng; Hung-Yu Shih; Pin Ouyang (Histochemistry and Cell Biology, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

A new viewpoint on risk control decision models for natural disasters - Chun-Pin Tseng; Cheng-Wu Chen; Yu-Ping Tu (Natural Hazards, 2011)

Monitoring and estimating scale-dependent hierarchical relationships between Sicyopterus japonicus density and stream habitat features in different seasons in northern Taiwan - Hsiao-Hsuan Yu; Yu-Pin Lin; Cheng-Long Wang (Environmental Monitoring and Assessment, 2011)

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth - His-Ming Wang; Show-Mei Chuang; Yu-Ching Su; Yi-Hui Li; Pin Ju Chueh (Cell Biochemistry and Biophysics, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Association of hypomethylation of LINE-1 repetitive element in blood leukocyte DNA with an increased risk of hepatocellular carcinoma - Jian-zhong Di; Xiao-dong Han; Wen-ye Gu; Yu Wang; Qi Zheng; Pin Zhang; Hui-min Wu; Zhong-zheng Zhu (Journal of Zhejiang University-SCIENCE B, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

Monitoring and identification of spatiotemporal landscape changes in multiple remote sensing images by using a stratified conditional Latin hypercube sampling approach and geostatistical simulation - Yu-Pin Lin; Hone-Jay Chu; Yu-Long Huang; Chia-Hsi Tang; Shahrokh Rouhani (Environmental Monitoring and Assessment, 2011)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Risk assessment of inhalation exposure to polycyclic aromatic hydrocarbons in Taiwanese workers at night markets - Ping Zhao; Kuo-Pin Yu; Chi-Chi Lin (International Archives of Occupational and Environmental Health, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Effects of land cover changes induced by large physical disturbances on hydrological responses in Central Taiwan - Nien Ming Hong; Hone-Jay Chu; Yu-Pin Lin; Dung-Po Deng (Environmental Monitoring and Assessment, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Joint Impact of Scaling and Hysteresis on NAPL Flow Simulation - Hung-Hui Chen; Liang-Cheng Chang; Hsin-Yu Shan; Jui-Pin Tsai (Environmental Modeling & Assessment, 2009)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Differential global genomic changes in rice root in response to low-, middle-, and high-osmotic stresses - Ting-chen Ma; Rong-jun Chen; Rong-rong Yu; Han-lai Zeng; Duan-pin Zhang (Acta Physiologiae Plantarum, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Antimicrobial effect and resistant regulation of Glycyrrhiza uralensis on methicillin-resistant Staphylococcus aureus - Ji-Won Lee; Young-Ju Ji; Mi-Hee Yu; Mi-Hyang Hwang Bo; Hwa-Jeong Seo; Sam-Pin Lee; In-Seon Lee (Natural Product Research, 2009)

Mapping and assessing spatial multiscale variations of birds associated with urban environments in metropolitan Taipei, Taiwan - Yun-Bin Lin; Yu-Pin Lin; Wei-Ta Fang (Environmental Monitoring and Assessment, 2008)

Geostatistical approaches and optimal additional sampling schemes for spatial patterns and future sampling of bird diversity - Yu‐Pin Lin; Ming‐Sheng Yeh; Dong‐Po Deng; Yung‐Chieh Wang (Global Ecology and Biogeography, 2008)
Aim To evaluate geostatistical approaches, namely kriging, co‐kriging and geostatistical simulation, and to develop an optimal sampling design for mapping the spatial patterns of bird diversity, estimating their spatial autocorrelations and selecting additional samples of bird diversity in a 2450 km 2 basin. Location Taiwan. Methods Kriging, co‐kriging and simulated annealing are applied to estimate and simulate the spatial patterns of bird diversity. In addition, kriging and co‐kriging with a genetic algorithm are used to optimally select further samples to improve the kriging and co‐kriging estimations. The association between bird diversity and elevation, and bird diversity and land cover, is analysed with estimated and simulated maps. Results The Simpson index correlates spatially with the normalized difference vegetation index (NDVI) within the micro‐scale and the macro‐scale in the study basin, but the Shannon diversity index only correlates spatially with NDVI within the micro‐scale. Co‐kriging and simulated annealing simulation accurately simulate the statistical and spatial patterns of bird diversity. The mean estimated diversity and the simulated diversity increase with elevation and decrease with increasing urbanization. The proposed optimal sampling approach selects 43 additional sampling sites with a high spatial estimation variance in bird diversity. Main conclusions Small‐scale variations dominate the total spatial variation of the observed diversity due to a lack of spatial information and insufficient sampling. However, simulations of bird diversity consistently capture the sampling statistics and spatial patterns of the observed bird diversity. The data thus accumulated can be used to understand the spatial patterns of bird diversity associated with different types of land cover and elevation, and to optimize sample selection. Co‐kriging combined with a genetic algorithm yields additional optimal sampling sites, which can be used to augment existing sampling points in future studies of bird diversity.

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)

Potential refugia in Taiwan revealed by the phylogeographical study of Castanopsis carlesii Hayata (Fagaceae) - YU‐PIN CHENG; SHIH‐YING HWANG; TSAN‐PIAO LIN (Molecular Ecology, 2005)
In this study, we examined spatial patterns of chloroplast DNA (cpDNA) variation in a total of 30 populations of Castanopsis carlesii Hayata (Fagaceae), a subtropical and temperate tree species, including 201 individuals sampled throughout Taiwan. By sequencing two cpDNA fragments using universal primers (the trn L intron and the trn V‐ trn M intergenic spacer), we found a total of 1663 bp and 21 polymorphic sites. These gave rise to a total of 28 cpDNA haplotypes. The level of differentiation among the populations studied was relatively high ( G ST = 0.723). Two ancestral haplotypes are widely distributed. The Central Mountain Ridge (CMR) of Taiwan represents an insurmountable barrier to the east–west gene flow of C. carlesii . Among the populations studied, three separated populations, at Lienhuachih, Fushan and Lichia, have high nucleotide diversity. Estimates of N ST – G ST for populations on both sides of the CMR indicate that no phylogeographical structure exists. According to the genealogical tree, number of rare haplotype and population genetic divergence, this study suggests that two potential refugia existed during the last glaciation: the first refugium was located in a region to the north of Hsuehshan Range (HR) and west of the CMR; the second refugium was located in south, especially southeastern Taiwan. In fact, the second refugium happens to be the same as that reported for Quercus glauca . A ‘star‐like’ genealogy is characteristic when all haplotypes rapidly coalesce and is a general outcome of population expansion. The neutrality test and mismatch distribution also suggest demographic expansion recovering from a bottleneck.

Multiple-Point Variance Analysis for Optimal Adjustment of a Monitoring Network - Yu-Pin Lin; Shaharokh Rouhani (Environmental Monitoring and Assessment, 2001)